(untitled) (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
The study of humanity from the perspective of the Qur’an occupies a central position in Islamic scholarship, as it explores the essence and deepest structure of human existence as a creation of Allah SWT. This paper aims to elaborate on the concept of human psychology according to the Qur’an and its contribution to the development of Islamic psychology. The study employs a qualitative approach using library research and applies a thematic exegesis method (tafsīr maudhū‘ī) to compile Qur’anic verses related to the human being (al-insān), the soul (nafs), and personality. The findings reveal that the Qur’an views the human being as a multidimensional entity composed of physical, spiritual, and intellectual elements. These three dimensions form an integral unity that establishes humanity as Allah’s vicegerent (khalīfah) on earth. The Qur’an uses the terms insān, basyar, and banī Ādam to describe various dimensions of humanity encompassing spiritual, biological, and social aspects. From the perspective of Islamic psychology, humans possess a dual potential —toward goodness or evil— manifested in the dynamics of nafs al-ammārah, nafs al-lawwāmah, and nafs al-muṭma’innah. Al-Ghazali’s thought on the four psychological dimensions (physical, vegetative, animalistic, and human) enriches the understanding of the complex structure of the human soul, which serves as the center of moral and spiritual activity.